Advent of phytobiologics and nano-interventions for bone remodeling: a comprehensive review. (2nd January 2023) - Gupta, Archita; Mehta, Sanjay Kumar; Kumar, Ashok; Singh, Sneha
Abstract: Bone metabolism constitutes the intricate processes of matrix deposition, mineralization, and resorption. Any imbalance in these processes leads to traumatic bone injuries and serious disease conditions. Therefore, bone remodeling plays a crucial role during the regeneration process maintaining the balance between osteoblastogenesis and osteoclastogenesis. Currently, numerous phytobiologics are emerging as the new therapeutics for the treatment of bone-related complications overcoming the synthetic drug-based side effects. They can either target osteoblasts, osteoclasts, or both through different mechanistic pathways for maintaining the bone remodeling process. Although phytobiologics have been widely used since tradition for the treatment of bone fractures recently, the research is accentuated toward the development of osteogenic phytobioactives, constituent-based drug designing models, and efficacious delivery of the phytobioactives. To achieve this, different plant extracts and successful isolation of their phytoconstituents are critical for osteogenic research. Hence, this review emphasizes the phytobioactives based research specifically enlisting the plants and their constituents used so far as bone therapeutics, their respective isolation procedures, and nanotechnological interventions in bone research. Also, the review enlists the vast array of folklore plants and the newly emerging nano-delivery systems in treating bone injuries as the future scope of research in the phytomedicinal orthopedic applications. Graphical Abstract: UF0001